Effect of separate and mixed rearing according to sex on fattening performance and carcass characteristics in Japanese quails (Coturnix coturnix Japonica) - Kul, Selim; Seker, Ibrahim; Yildirim, Ozge (Archiv Fur Tierzucht, 2006)
The objective of this study was to investigate the effect of sex of Japanese quails (Coturnix coturnix Japonica) on fattening performance and carcass characteristics. The quail chicks were divided into three groups, made up of 96 males or 92 females or 36 individuals of each sex, resulting in a total of 256 chicks. The chicks in the groups were raised using the same feeding regime (24% CP, 2900 kcal/kg ME) and housing conditions for 42 days. There were significant (P < 0.01) differences between male and female groups in weekly live body weight (1bw) gain values on day 35, in average live body weight gain on days 35 and 42, and in lbw gain values between days 14 and 42. Slaughter weight and liver weight were significantly different between groups (P < 0.01). The differences between the two sex in mixed group in average body weight gain, average lbw on days 35 and 42, average lbw gain, Ibw gain between days 14 and 42, slaughter weight, hot carcass yield, and liver weight were found significant (P < 0.01). Lbw, lbw gain, feed consumption, slaughter weight, hot carcass yield, weights of heart, liver and giblets were higher in female quails while feed conversion rate was lower. As a result, these data suggest that separate raising of male and female Japnese quails might be more advantageous.
Keywords: gender; fattening performance; slaughter and carcass characteristics; Japanese quails